Risk Defect on Du Base Frame Product - Adriyadhi S, Agyl; Singgih, Moses Laksono (Institut Teknologi Sepuluh Nopember, 2019)
During the production process DU base frame product has been found quite a defect occurrence. Defects occurring during the production process of course affect the cost, time and quality of the product production of PT. X, so it is required a handling to overcome the risk of defects that occur so that the product is free from the risk of defects that do not and improve product quality. The method that can overcome the problem above is to predict the risk of product defect by designing a risk management process framework. The risk management planning process is a stage identifying the risk of defects that have occurred or the risk of malformed defects occurred and then conducting a risk-defect analysis, then evaluating the risks of such defects and risk treatment and Monitoring and review. There are also tools and methods used in this risk management study are fishbone and FMEA. Fishbone is used as a tool as a method to cause identification while FMEA is used in risk analysis to determine risk priority number (RPN). From RPN defects that have the highest value will be taken risk evaluation and risk treatment to prevent the same defect. With this research in hopes of the results of quality, cost and production time in DU Base Frame products can remain consistent and give rise to the awareness of the personnel involved in the product manufacturing process. From risk mitigation results found there are 4 out of 56 risk cases that belong to the high-risk category in the process of milling (RPN 288), blasting (RPN 288 & 224) and painting (256). These risks are then conducted advice on the improvements that are discussed with the team and the costumer and the result of defects that occur reduced even eliminated. The importance of the detailed procedures and the awareness of each personnel involved becomes one of the keys to avoid risk in the production process of a product